Pelatihan Teknik Khitobah Bahasa Arab di Madrasah Aliyah Al-Hamidy Banyuanyar Pamekasan - Mohammad Fauzi; Subairi; Adib Ibrohimi; Hairul Imam Mustafa (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2025)
Abstract This community service aims to improve the skills of students of Madrasah Aliyah Al-Hamidy Banyuanyar Pamekasan in composing and delivering Arabic sermons, as well as encouraging social change among students. The main focus of this service is improving public speaking skills and delivering da'wah messages effectively. The method used in this service is service learning by applying the scientific field of Arabic language sermon techniques based on practice, which involves sermon simulations and group discussions to improve students' speaking techniques. The results of this service show an increase in students' speaking skills, as well as the emergence of social awareness and local leaders who are active in da'wah. In addition, discussion groups were created based on da'wah practices and sharing knowledge. This service concludes that the development of practice-based speaking skills can improve students' da'wah abilities, while active participation encourages positive social change in the madrasah environment and society. Keywords: Arabic Sermons, Students Abstrak Pengabdian masyarakat ini bertujuan untuk meningkatkan keterampilan murid Madrasah Aliyah Al-Hamidy Banyuanyar Pamekasan dalam menyusun dan menyampaikan khutbah Bahasa Arab, serta mendorong perubahan sosial di kalangan murid. Fokus utama pengabdian ini adalah peningkatan kemampuan berbicara di depan umum dan penyampaian pesan dakwah secara efektif. Metode yang digunakan dalam pengabdian ini adalah service learning dengan menerapkan bidang keilmuan teknik khitobah bahasa arab berbasis praktik, yang melibatkan simulasi khutbah dan diskusi kelompok untuk memperbaiki teknik berbicara murid. Hasil dari pengabdian ini menunjukkan peningkatan keterampilan berbicara murid, serta munculnya kesadaran sosial dan pemimpin lokal yang aktif dalam dakwah. Selain itu, tercipta kelompok-kelompok diskusi yang berbasis pada praktek dakwah dan berbagi ilmu. Kesimpulan dari pengabdian ini adalah bahwa pengembangan keterampilan berbicara berbasis praktik dapat meningkatkan kemampuan dakwah murid, sementara partisipasi aktif mendorong perubahan sosial positif di lingkungan madrasah dan masyarakat. Kata Kunci: Khitobah Bahasa Arab, Murid